2021
DOI: 10.31246/mjn-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutrition knowledge and nutrition practice among Malaysian adolescent handball athletes

Abstract: Introduction: Previous literature suggests that good nutrition knowledge does not necessarily translate into desired eating behaviours among adolescent athletes, which may affect their sports performance. The purposes of the study were twofold, which were to examine nutrition knowledge and practice between the sexes, and to evaluate the magnitude of relationship between nutrition knowledge and practice among adolescent handball athletes in Malaysia. Methods: Three hundred and twelve male and female adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…This aligned with previous research showing a positive association between nutrition knowledge and practices among adolescent athletes ( 30–32 ), the positive correlation between dietary intake and SNK among Adolescent Soccer Players supports this finding ( 33 ). Notably, our research outcomes are contrasts with a study demonstrating that possessing knowledge does not always result in the adoption of good dietary practices ( 34 ). The positive association between SNK and FH emphasizes the pivotal role of education in shaping athletes’ dietary choices ( 14 , 35 ).…”
Section: Discussioncontrasting
confidence: 97%
“…This aligned with previous research showing a positive association between nutrition knowledge and practices among adolescent athletes ( 30–32 ), the positive correlation between dietary intake and SNK among Adolescent Soccer Players supports this finding ( 33 ). Notably, our research outcomes are contrasts with a study demonstrating that possessing knowledge does not always result in the adoption of good dietary practices ( 34 ). The positive association between SNK and FH emphasizes the pivotal role of education in shaping athletes’ dietary choices ( 14 , 35 ).…”
Section: Discussioncontrasting
confidence: 97%
“…Similarly, Masoga et al [ 54 ] reported that the dietary practices of athletes involved in the sport of soccer did not adhere to soccer nutritional guidelines established by the International Society of Sports Nutrition. Furthermore, Jusoh et al [ 55 ] did not observe significant differences in the knowledge and practice of nutrition between sexes in handball. However, the results showed that nutrition knowledge had a significant but weak positive correlation with eating habits among athletes.…”
Section: Optimizing Athlete Performance Through Nutrition Insightsmentioning
confidence: 98%
“…Three studies did not report the specific sports played by the study population. Eighteen studies recruited participants from one type of sport including swimming ( 9 , 22 , 31 , 49 ) , basketball ( 28 , 30 , 44 ) , soccer ( 41 , 43 ) , gymnastics ( 21 ) , ballet ( 20 ) , rugby ( 57 ) , table tennis ( 23 ) , American football ( 24 ) , cross-country skiing ( 38 ) , handball ( 37 ) , volleyball ( 29 ) and synchronised swimming ( 40 ) . The remaining studies represented various sports, including track and field ( 47 ) , aesthetic sports ( 39 ) , endurance sports ( 34 , 35 ) and various team and individual sports ( 25 27 , 36 , 42 , 45 , 46 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed quality assessments for all included studies, with scores assigned for each validity criterion of the Academy of Nutrition and Dietetics ‘Quality Criteria Checklist: Primary Research’ ( 52 ) , are available in the supplementary material (online Supplementary Table ). Only two studies received an overall ‘positive’ rating ( 34 , 37 ) , with all remaining studies ( n 30) receiving ‘neutral’ ratings, indicating a moderate quality level. The main reasons for neutral ratings were related to the selection of study subjects (criterion 2) and the use of valid and reliable measurement tools (criterion 7) followed by an inadequate description of study settings (criterion 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation